The patient perspective in the era of personalized medicine: What about scanxiety?. (9th April 2021) - Custers, José A. E.; Davis, Lucy; Messiou, Christina; Prins, Judith B.; van der Graaf, Winette T. A.
Abstract : Frequency of scanning has accelerated in the era of personalized medicine and is related, but not restricted, to the exploding number of clinical trials for new cancer treatments. Particularly in drug trials, but also in clinical practice, patients are followed up by scans frequently, which may vary from every 6 to 12 weeks until progression. The authors aimed to raise awareness for this underreported but widely present "Sword of Damocles" scan‐related issue also referred to as 'scanxiety.'